Incidence of Vestibular Schwannoma in Taiwan from 2001 to 2012: A Population-Based National Health Insurance Study. (October 2018) - Koo, Malcolm; Lai, Jen-Tsung; Yang, Edward Yih-Liang; Liu, Tien-Chen; Hwang, Juen-Haur
Objectives: Vestibular schwannomas, also known as acoustic neuromas, are slow-growing tumors that may lead to asymmetric hearing loss, unilateral tinnitus, and vertigo. Population-based data are lacking regarding the incidence of vestibular schwannoma in Asian populations. The aim of this study was to investigate the incidence of vestibular schwannoma in Taiwan using data from a population-based health claim database. Subjects and Methods: Patients aged 20 years and over with incident cases of vestibular schwannoma between January 1, 2001, and December 31, 2012, were identified from the Longitudinal Health Insurance Database 2000 of the National Health Insurance Research Database (NHIRD), Taiwan, based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) code 225.1. Only those patients who had received a magnetic resonance imaging scan prior to the diagnosis of vestibular schwannoma were considered as definitive cases. Results: 206 cases of vestibular schwannoma were identified during the interval 2001 to 2012. The overall annual incidence was 2.66 per 100 000 persons (95% confidence interval, 2.32-3.05). The annual incidence rate varied throughout the study period, ranging from 1.74 to 3.72 per 100 000 persons. The highest incidence rate of 4.86 per 100 000 persons was observed in the age group of 60 to 69 years. Conclusions: Based on data from the NHIRD in Taiwan for the years 2001 to 2012, the average annual incidence rate of vestibular schwannoma was found to be 2.66 per 100 000 persons.